Impaired host resistance to Salmonella during helminth co-infection is restored by anthelmintic treatment prior to bacterial challenge. - Tara P Brosschot; Katherine M Lawrence; Brandon E Moeller; Mia H E Kennedy; Rachael D FitzPatrick; Courtney M Gauthier; Dongju Shin; Dominique M Gatti; Kate M E Conway; Lisa A Reynolds (Public Library of Science (PLoS), 2021)
Intestinal helminth infection can impair host resistance to co-infection with enteric bacterial pathogens. However, it is not known whether helminth drug-clearance can restore host resistance to bacterial infection. Using a mouse helminth-Salmonella co-infection system, we show that anthelmintic treatment prior to Salmonella challenge is sufficient to restore host resistance to Salmonella. The presence of the small intestine-dwelling helminth Heligmosomoides polygyrus at the point of Salmonella infection supports the initial establishment of Salmonella in the small intestinal lumen. Interestingly, if helminth drug-clearance is delayed until Salmonella has already established in the small intestinal lumen, anthelmintic treatment does not result in complete clearance of Salmonella. This suggests that while the presence of helminths supports initial Salmonella colonization, helminths are dispensable for Salmonella persistence in the host small intestine. These data contribute to the mechanistic understanding of how an ongoing or prior helminth infection can affect pathogenic bacterial colonization and persistence in the mammalian intestine.